Implementasi Penggunaan Kitab Matnu Al-Ajurumiyyah Pada Madrasah Tsanawiyah - Titin Fatimah; Muhammad Paris Fauzi; Atna Akhiryani (Albariq: Jurnal Pendidikan Bahasa Arab, 2021)
This research aims at providing a clear description about the implementation, the obstacle and the technique solution of the use of Mat’nu Al-Ajurumiyyah book to the students at Raudhatul Musthafa Lil Khairaat Islamic Boarding School Palu in Arabic learning. This research employed descriptive qualitative method. The result of this research showed that Arabic learning is one of featured subjects at Raudhatul Musthafa Lil Khairaat Islamic Boarding School Palu. This is because Arabic subject is required to understand Al Qur’an and Al Sunnah.